Georgia : Assessing Economy Wide Indirect Impacts of East-West Highway Investments through CGE Modeling - World Bank (Washington, DC, 2015)
The objective of this study was to assess the economy wide indirect benefits of investments in the East West highway (EWH). This study has used a computable general equilibrium (CGE) model, which simulates indirect benefits associated with the completion of the upgraded road corridor. The transmission channel modeled is the reduction in transportation costs - reduction in vehicle operating costs, and time savings - resulting from the investments in the EWH. A CGE model is a simultaneous equation system that consists of equations representing various economic relationships for different economic agents, such as producers and households. CGE models are commonly used by countries and international financial institutions to simulate policy interventions to determine economy-wide impacts. This study involved modifying the existing social accounting matrix (SAM) and CGE model in order to carry out simulations to answer the question of economy wide impacts of the EWH investments, including impacts on real gross domestic product (GDP) growth, jobs, and trade, as well as impacts on households disaggregated by income. It aims to answer the following questions: how will the EWH lower the transportation costs for producers of goods and services?; what are the economy wide impacts of the EWH on employment, real GDP growth, trade, and household income?; and can the EWH help bridge the existing economic divide between rural and urban areas in Georgia? The study is aims to simulate quantitatively how the EWH as a large-scale infrastructure investment program can bring significant stimulus to foster economic growth and welfare in Georgia.